Corporate Criminal Liability in Tax Offenses - Reynold Simanjuntak; Aldy Yohanes Manueke (JUSTISI, 2026)
This study aims to analyze the legal framework governing corporate criminal liability in the context of tax offenses. This study uses a normative juridical method with a statute approach, a case approach, and a conceptual approach. The novelty of this research lies in its critical analysis of the inconsistency found in tax crime cases: a discrepancy between the judges' legal reasoning, which acknowledges corporate fault, and the final verdicts, which ultimately only impose criminal sanctions on the corporate officers. The results highlight a significant regulatory gap, as the current tax criminal framework lacks explicit corporate sanctions. In practice, this issue is compounded by judicial inconsistency, where court rulings impose penalties solely on corporate directors, even when the corporation's role in profiting from the crime is acknowledged by the court. The  conclusion of  the  research that a normative vacuum in the undang-undang perpajakan, compounded by judicial inconsistencies regarding corporate tax offenses, results in significant legal uncertainty. Consequently, legislative amendments are required to unequivocally establish the principles of corporate accountability.